2006
DOI: 10.1186/1472-6904-6-7
|View full text |Cite
|
Sign up to set email alerts
|

Finasteride induced depression: a prospective study

Abstract: BackgroundFinasteride is a competitive inhibitor of 5 alpha-reductase enzyme, and is used for treatment of benign prostatic hyperplasia and androgenetic alopecia. Animal studies have shown that finasteride might induce behavioral changes. Additionally, some cases of finasteride-induced depression have been reported in humans. The purpose of this study was to examine whether depressive symptoms or anxiety might be induced by finasteride administration.MethodsOne hundred and twenty eight men with androgenetic al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(84 citation statements)
references
References 43 publications
5
74
0
3
Order By: Relevance
“…The results are similar to literature data and according to BDI are as follows: 12 points for psoriasis, 12.11 ±7.50 points for male pattern alopecia and 5.87 ±4.68 points in the course of hidradenitis suppurativa [23][24][25]. In our study, 42% of patients suffered from depression of different severity before the therapy, which dropped to 18% after the intervention.…”
Section: Discussionsupporting
confidence: 79%
“…The results are similar to literature data and according to BDI are as follows: 12 points for psoriasis, 12.11 ±7.50 points for male pattern alopecia and 5.87 ±4.68 points in the course of hidradenitis suppurativa [23][24][25]. In our study, 42% of patients suffered from depression of different severity before the therapy, which dropped to 18% after the intervention.…”
Section: Discussionsupporting
confidence: 79%
“…As 5α-reductase represents the rate-limiting step enzyme in the synthesis of the GABAergic steroid allopregnanolone, it is assumed that downregulation of 5α-reductase mediates aggressive behavior, anxiety and cognitive dysfunction observed in socially isolated mice. Inhibition of 5α-reductase by finasteride, a compound used for the treatment of benign prostatic hyperplasia and androgenetic alopecia, induced depression-like states in a prospective study of 128 men [24]. Furthermore, mice treated with finasteride display depression-like behavior in the forced swim test [25].…”
Section: Discussionmentioning
confidence: 99%
“…Several research studies have investigated the adverse psychological effects of finasteride (Altomare & Capella, 2002;Ganzer, Jacobs, & Iqbal, 2014;Irwig, 2012;Melcangi et al, 2013;Rahimi-Ardabili, Pourandarjani, Habibollahi, & Mualeki, 2006;Traish, Hassani, Guay, Zitzmann, & Hansen, 2011). In 2002, researchers investigating depression as an adverse effect of finasteride, researchers reported that men (n = 17) who had taken 1 mg per day of finasteride for AGA developed moderate to severe depression during treatment and stated that further studies were needed (Altomare & Capella, 2002).…”
Section: Introductionmentioning
confidence: 99%